2010
DOI: 10.2478/v10181-010-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tramadol and metabolites after injective administrations in dogs

Abstract: The aim of this study was to determine the pharmacokinetics of tramadol and its main metabolites after IV and IM injections. The pharmacokinetic cross-over study was carried out on 6 healthy male beagle dogs. Tramadol was administered by intravenous (IV) and intramuscular (IM) injection at 4 mg/kg. Tramadol and its main metabolites O-desmethyl-tramadol (M1), N-,N-didesmethyl-tramadol (M2) and N-,O-didesmethyl-tramadol (M5) concentrations were measured in plasma samples by a HPLC coupled with fluorimetric detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 12 publications
0
24
1
3
Order By: Relevance
“…In humans, it was reported that the minimum effective plasma concentrations of tramadol was 287.7 ng/ml [16]. Giorgi et al [6] reported that the minimum effective plasma concentration of tramadol as calculated for humans had been maintained for about 6-7 hr following a single IV administration of 4 mg/kg tramadol in dogs. We previously reported [10] that the plasma concentration of tramadol gradually decreased over time from approximately 2,000 ng/ml at 5 min to 500 ng/ml at 120 min after a single IV dose of 4 mg/kg tramadol in older dogs (8-10 years old) anesthetized with sevoflurane 1.3 MAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, it was reported that the minimum effective plasma concentrations of tramadol was 287.7 ng/ml [16]. Giorgi et al [6] reported that the minimum effective plasma concentration of tramadol as calculated for humans had been maintained for about 6-7 hr following a single IV administration of 4 mg/kg tramadol in dogs. We previously reported [10] that the plasma concentration of tramadol gradually decreased over time from approximately 2,000 ng/ml at 5 min to 500 ng/ml at 120 min after a single IV dose of 4 mg/kg tramadol in older dogs (8-10 years old) anesthetized with sevoflurane 1.3 MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, especially in human studies, use the plasma concentration of M1 to determine the analgesic effect of tramadol, because the evidence indicates that M1 is responsible for most of the therapeutic effects rather than the parent drug [4]. Giorgi et al [6] stated that M1 might not be responsible for the major clinical effectiveness in dogs, because M1 was detected at a lower concentration than the minimum effective plasma concentration (40 ng/ml) reported in humans [7]. However, a higher M1 concentration (65 ± 16 ng/ml) was detected in dogs infused tramadol at a rate of 1.3 mg/kg/hr CRI following 1.5 mg/kg IV [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been used for some time now, our understanding and ability to predict the time course of its pharmacological effects in animals are still hampered by the presence of active metabolites and the coexistence of opioid and non-opioid mechanisms. Recently, T has been reported to be metabolized faster to inactive metabolites N-desmethyl tramadol (M2) and O,N-didesmethyl tramadol (M5), in goats (Sousa et al, 2008), dogs (McMillan et al, 2008;Giorgi et al, 2009a;2009b;2009c;2009d;2010a;Kukanich and Papich, 2011), horses (Giorgi et al, 2007;Shilo et al, 2008;Cox et al, 2010;Giorgi et al, 2010b), llamas , alpacas (Giorgi et al, 2010c), peafowl (Black et al, 2010), hawks than in cats (Pypendop and Ilkiw, 2008). The use of T has also been suggested for zoo animals .…”
Section: Tramadolmentioning
confidence: 99%
“…Ten min later (Giorgi et al 2010;Slingsby et al, 2015), anaesthesia was induced by intravenous (IV) administration of 2 mg/Kg propofol boluses (Cristalia Laboratories, Itapira, Brazil), repeated every 60 sec until loss of palpebral reflex. The total propofol induction dose (PID) was recorded.…”
Section: Experimental Designmentioning
confidence: 99%